PTU-106 Improved Survival and Independance from Parental Nutrition for Patients with Intestinal Dysmotility. (17th August 2016) - Appleby, R; Yu, C; Nightingale, J
Abstract : Introduction: Patients receiving home parental nutrition (HPN) for intestinal dysmotility have a poor 5 years survival of 68% and independence from HPN at 5 years of 12% ( Lloyd et al. 2006 1 ). Only abdominal malignancy patients fared worse. We aimed to compare the same outcomes, at the same centre 10 years since this study to see if changes in practice had impacted these outcomes. Methods: An institutional database of patients referred to the Leonard Jones Intestinal Failure Unit at St Marks Hospital was interrogated for patients who started HPN between 1/1/04-1/10/15 and had the primary cause of their intestinal failure recorded as 'dysmotility' or 'other'. The discharge and outpatient letters of those patients were inspected. Patients were excluded if there was any mechanical obstruction, IBD or coeliac disease prior to starting HPN or insufficient clinical information to rule these out. Measured outcomes were survival, intestinal transplant and independence from HPN. Results: 159 patients were identified as potentially having dysmotility. 91 were excluded because dysmotility was not the primary cause of the intestinal failure or there was insufficient information, leaving 68 for the final analysis. The median age of this cohort was 39 years (range 16–78) and 19% were male. In total there were 471.2 years of follow up since starting HPN (median 4.4 (range 0.03–26.9)). 21 patients (31%) had a bowel resection before starting HPN. Overall survival 91%, (n = 62, 5 died on HPN, 1 off HPN), intestinal transplant 4% (n = 3, all successful), 29% (n = 17) were independent of HPN. 5 year outcomes were available for 18 patients. Survival at 5 years was 84% and independence from HPN was 40%. There were no transplants in this group. 23 patients had a diagnosis of chronic intestinal pseudo-obstruction (CIPO), 18 primary and 5 secondary, median follow up was 4.2 years. Overall survival was 91% and independence from HPN was 40%. 4 had positive histological diagnosis of neuropathy and 4 of myopathy. Both secondary CIPO (n = 5) and neuropathic bowel (n = 4) were predictive of independence from HPN compared to other dysmotility diagnoses, secondary CIPO odds ratio 0.03 (95%CI 0.0015–0.6, p < 0.05), neuropathy odds ratio 0.098 (95%CI 0.009–1.0, p = 0.05). Conclusion: Our recent data implies improved outcomes on HPN for patients with dysmotility, particularly patients with secondary CIPO. This may be due to advances in treatment of underlying conditions. Reference: 1 Lloyd DA, Vega R, Bassett P, Forbes A, Gabe SM. Survival and dependence on home parenteral nutrition: experience over a 25-year period in a UK referral centre. Alimentary Pharmacol Ther 2006;24 :1231–40 Disclosure of Interest: None Declared